1069 Overutilization of CT Scan of the Brain in the Diagnosis of Hepatic Encephalopathy: Choosing Wisely - Khan, Ahmad; Sohail, Abdullah; Cipriani, Allison; McDaniel, Bryce A.; Farooq, Junaid; Chowdhry, Monica; Singh, Shailendra (The American journal of gastroenterology, 2019)
INTRODUCTION:Hepatic encephalopathy (HE) is a clinical diagnosis and rarely requires neuroimaging. Hepatic encephalopathy (HE) is the most common diagnosis for patients with cirrhotic patients presenting with altered mental status (AMS). It is a clinical diagnosis, and computed tomography (CT) of the brain does not contribute to the diagnostic or grading information. However, patients with cirrhosis are at increased risk of intracerebral hemorrhage, and therefore, CT scans are usually performed to rule out other etiologies of AMS, which may lead to overutilization of CT scans. There is limited data on the magnitude and yield of CT scan utility in the workup for HE. This study aims to assess the magnitude and yield of CT scan for the workup of HE in a large tertiary care hospital.METHODS:An electronic medical query for adult patients discharged from our center between September 2016 to June 2019 with ICD-10 codes for liver cirrhosis and its complications was made. A total of 300 patient charts were randomly selected for detailed review. Patients with an established diagnosis of advanced dementia, stroke, intracranial tumor, or bleed were excluded. We collected patient demographics, admission records, readmissions, laboratory values, and imaging records.RESULTS:A total of 214 patients met our search criteria. Out of these, 64 patients admitted with a complaint of AMS were included in the final analysis. The mean age of these patients was 61 ± 9 years, and 54% were males. A total of 152 HE-related hospitalizations were recorded for these 64 patients (an average of 2.3 admissions per patient). In the study duration, a total of 178 brain CT scans were performed for 152 hospitalizations. Out of the total 178 scans, only 2 CT (1.1%) scans revealed intracranial bleed leading to change in diagnosis or management. Notably, 12 (18.75%) patients had multiple CT scans during a single hospitalization.CONCLUSION:The yield of CT scan brain in patients with an established diagnosis of hepatic encephalopathy is low (1%) and usually does not influence the diagnosis or management. CT scans are likely overutilized, leading to unnecessary excessive radiation exposure to the patients and increases the total costs of hospitalization. Institutional efforts should be implied for the judicious use of CT scans in patients with HE. Further large multicenter studies are needed.